L’effet d’un « déjà-là » sur la pratique d'un enseignant : le point de vue de la didactique clinique de l’EPS - Hejer Ben Jomaâ Ben Hsouna; André Terrisse (Recherches en Éducation)
In this study, the singular logic of teaching of a teacher of physical and sporting education (PSE) is examined (Terrisse, 2003). In fact this article aims at identifying the traces of his “déjà-là” according to his singular history (Carnus, 2009) in his teaching. In this context, we analyze the differentiation of didactic abstract reference tables and teaching practices according to the personal resources translated here into terms of personal expertise of a teacher in a physical and sporting activity (PSA). The didactic analysis compared, by two teachings contrasted for the same teacher, and the case study of his verbatim and of his practice (six sessions of physical and sporting education, four interviews) supported the arguments regarding the importance of subjective foundations of knowledge transmission act in service of a clinical vision on the professional act.